Siegel disks of the tangent family - Cui, Weiwei; Nie, Hongming (Annales Fennici Mathematici, 2021)
We study Siegel disks in the dynamics of functions from the tangent family. In particular, we prove that a Siegel disk is unbounded if and only if the boundary of its image contains at least one asymptotic value. Moreover, by using quasiconformal surgery we also construct functions in the above family with bounded Siegel disks.